Carbon emission and financial development under the “double carbon” goal: Considering the upgrade of industrial structure - Yang, Wen-Jie; Tan, Meng-Zhuo; Chu, Shun-Ho; Chen, Zhen (Frontiers in Environmental Science, 2023)
Financial development is the impetus for economic advancement and takes the lead in achieving green development and an economy with low carbon. Under this background, this article decides on the panel data from 283 Chinese cities from 2006 to 2019 to empirically analyze the impact of financial advancement upon carbon emissions and uses the advanced industrial constitution as regulatory and intermediary variables to explore whether there is a regulatory role and transmission effect between the financial advancement and carbon emissions. The consequences indicate that: (1) Financial advancement wields an evident active influence over carbon emissions. Additionally, the upgrading of industrial structures wields an evident positive impact on carbon emissions. (2) Looking at the upgrading of the industrial constitution as the regulating variable, the upgrading of the industrial constitution exerts a prohibitive impact on financial development and carbon emissions; As an intermediary variable, the industrial constitution promotion exerts a partial intermediary impact between financial advancement and carbon emissions. (3) High level of financial advancement and high-caliber industrial constitution promotion (I), poor financial development and high-caliber industrial structure upgrading (II), poor financial development and poor industrial constitution promotion (III) The financial advancement of the urban agglomeration exerts an evident active effect upon carbon emissions. There exists a medium impact of industrial structure upgrading. The medium impact in category I urban agglomeration accounts for the largest proportion of the total effect. Simultaneously, the promotion of the industrial constitution of type I urban agglomeration has a prohibitive impact on financial development and carbon emissions, while the promotion of the industrial structure of type III urban agglomeration has a catalytic effect on carbon emissions and financial advancement.